2022
DOI: 10.1111/ijn.13042
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a mobile oral care app on oral mucositis, pain, nutritional status, and quality of life in patients with head and neck cancer: A quasi‐experimental study

Abstract: Aim: The aim of this work is to explore the effectiveness of a mobile app to support oral mucositis care to improve the nutritional status and reduce the occurrence of oral mucositis of patients with head and neck cancer undergoing concurrent chemoradiotherapy.Background: Concurrent chemoradiotherapy is the optimal treatment for head and neck cancer, but oral mucositis and malnutrition are common complications.Design: Quasi-experimental study using a pre-post design was used in this work.Method: Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 39 publications
0
17
0
1
Order By: Relevance
“…Lin et al [ 24 ] developed an oral care mobile app to provide medical health information and oral mucosal care advice to patients during radiotherapy for HNC. The results of the study showed that the Patient-Generated Subjective Global Assessment scores of the group using mHealth technology were significantly lower than those of the control group at all 3 nodes during the intervention.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al [ 24 ] developed an oral care mobile app to provide medical health information and oral mucosal care advice to patients during radiotherapy for HNC. The results of the study showed that the Patient-Generated Subjective Global Assessment scores of the group using mHealth technology were significantly lower than those of the control group at all 3 nodes during the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (n=9, 69.2%) measured and evaluated the HRQoL. Of these, 6 (66.7%) studies [ 14 , 19 , 21 - 24 ] used the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC-QLQ-C30) and the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 35 and Head and Neck Module (EORTC-QLQ-H&N35), 2 (22.2%) studies [ 13 , 15 ] used the Functional Assessment of Cancer Therapy—Head and Neck (FACT-H&N) scale, 2 (22.2%) studies [ 16 , 19 ] used the HRQoL scale, and 1 (11.1%) study [ 17 ] used the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire and Provisional 25-item Information Module (EORTC-QLQ-INFO-25) to assess the QoL of survivors of HNC.…”
Section: Resultsmentioning
confidence: 99%
“…Similar findings were identified in a study conducted by Lin et al, to assess the effectiveness of “mobile oral care app,” which had an educational content to improve QOL. The results of this study showed significant improvement in QOL among the participants of intervention group ( p < 0.001) [ 26 ]. The literature supports the benefits of exercise therapy and psychosocial programmes in improving the QOL among HNC patients [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 98%
“…17 Mobile health provides patients with access to informative animations, healthcare knowledge, and a platform for communication, enabling repetitive learning. 18 The ideal mHealth will meet patients' needs and enhance convenience and efficiency in clinical settings. 19,20 However, to our knowledge, current applications of mHealth in HNC are mainly focused on remote triage, 21,22 disease detection, 23,24 and symptom management, 25,26 leaving patients' diverse needs unaddressed, including psychology, nutrition, and physical activity.…”
mentioning
confidence: 99%
“…It has been widely used in oncology 17 . Mobile health provides patients with access to informative animations, healthcare knowledge, and a platform for communication, enabling repetitive learning 18 . The ideal mHealth will meet patients' needs and enhance convenience and efficiency in clinical settings 19,20 .…”
mentioning
confidence: 99%